Key Determinants of Family-Centered Care for Children with Leukemia - Palupi, Rini; Kusuma, Anggi; Yeni, Rizki; Solikha, Khansa Nadifa (International Journal of Contemporary Sciences (IJCS), 2024)
This study examines the relationship between health status, parental knowledge, and parental attitudes with the application of family-centered care (FCC) for children with leukemia at Abdul Moelok Regional Hospital, Lampung Province. Using a quantitative approach with a cross-sectional design, 92 respondents were selected from a population of 1,200 leukemia patients treated between 2021 and 2022. Data were collected through a validated questionnaire that measured parental knowledge, attitudes, and health status, with analysis conducted using the gamma correlation test. The results indicate significant relationships between health status, parental knowledge, and parental attitudes with the implementation of FCC. Factors such as age, education, income, caregiving duration, and disease length influenced the health status and FCC application. The study also reveals that caregivers face challenges in providing care, particularly due to financial burdens and physical strain, impacting their quality of life. Additionally, cultural factors affect how parents communicate the diagnosis to children, with some families delaying disclosure based on cultural norms.